2002
DOI: 10.1207/s15327752jpa7902_14
|View full text |Cite
|
Sign up to set email alerts
|

Using the PAI With an Eating Disordered Population: Scale Characteristics, Factor Structure, and Differences Among Diagnostic Groups

Abstract: Psychometric properties of the Personality Assessment Inventory (PAI; Morey 1991) within an eating disordered sample seeking treatment (N = 238) and differences among eating disorder diagnostic groups on the PAI were examined. The PAI showed acceptable alpha coefficients, item-total correlations, and interitem correlations. The factor structure was similar to that reported by Morey (1991), with the addition of another factor related to interpersonal coolness and distance. Those with binge eating disorder (BED)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
42
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 18 publications
9
42
1
1
Order By: Relevance
“…The factor may be an indicator of general level of disturbance and impairment in functioning. This factor is very similar to the first factor reported by Morey (1991) in the PAI Manual, as well as the first factor identified by Tasca et al (2002), Schinka (1995), and Deisinger (1995) in their studies of the PAI factor structure in eatingdisordered, alcohol-dependent, and normal samples, respectively. Note.…”
Section: Factor Analysessupporting
confidence: 80%
See 2 more Smart Citations
“…The factor may be an indicator of general level of disturbance and impairment in functioning. This factor is very similar to the first factor reported by Morey (1991) in the PAI Manual, as well as the first factor identified by Tasca et al (2002), Schinka (1995), and Deisinger (1995) in their studies of the PAI factor structure in eatingdisordered, alcohol-dependent, and normal samples, respectively. Note.…”
Section: Factor Analysessupporting
confidence: 80%
“…The coefficients are acceptable and very similar to those reported by Morey (1991). The mean alpha for full scales listed in Table 1 is .79, which is virtually identical to the mean alpha (.78) for Morey's clinical sample and the mean alpha (.82) reported by Boone (1998) and Tasca et al (2002) on samples of psychiatric inpatients and eating disorder patients, respectively. The lowest obtained value from the clinical and interpersonal scales was from the Drug Problems (␣ ϭ .58) scale, which appeared to be caused by low item endorsements and limited variance of responses.…”
Section: Reliability Analysessupporting
confidence: 71%
See 1 more Smart Citation
“…10 Research also suggests that, like eating disorders themselves, the eating disorderinterpersonal problem relation is stronger in women than men, 11 and that women with bulimia nervosa tend to experience more interpersonal difficulties than women with anorexia nervosa. 12,13 Brown et al 14 found that, whereas women with binge-eating disorder tend to eat more than others and women with anorexia nervosa tend to eat less than others across social situations, women with bulimia nervosa tend to eat more on average, but less when social cues regarding food intake are elicited, further suggesting an important relation between interpersonal problems and bulimic features.…”
Section: Introductionmentioning
confidence: 99%
“…The Personality Assessment Inventory (PAI) is a widely available assessment tool that has been used across different settings with different populations [1][2][3][4][5][6][7][8]. To date, however, there has been little research on using the PAI in an eating disordered population.…”
Section: Introductionmentioning
confidence: 99%